2014
DOI: 10.5433/1679-0359.2014v35n4suplp2809
|View full text |Cite
|
Sign up to set email alerts
|

Crioprotetores para o resfriamento de embriões de piracanjuba Brycon orbignyanus (Valenciennes, 1850)

Abstract: ResumoO objetivo deste trabalho foi avaliar a eficiência dos crioprotetores para o resfriamento de embriões de B. orbignyanus. Foram selecionados 1.400 embriões viáveis, na fase de pós-gastrulação e submetidos ao resfriamento a -8ºC com diferentes combinações de crioprotetores permeáveis (Metanol e dimetilsulfóxido -DMSO 9% ou associados 4,5%) combinados à crioprotetores não permeáveis (Sacarose e Glicose, 17%). Para cada tratamento, 200 embriões foram alocados em tubos de vidro "vacutainer" e submetidos ao pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This characteristic is present in embryos after cooling and was observed by Fornari et al . (2014), although in cooled embryos of piracanjuba ( Brycon orbignyanus ). According to the author, such a characteristic is used as evidence of ice crystal formation, which causes embryonic mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is present in embryos after cooling and was observed by Fornari et al . (2014), although in cooled embryos of piracanjuba ( Brycon orbignyanus ). According to the author, such a characteristic is used as evidence of ice crystal formation, which causes embryonic mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Hubálek (2003) considered a concentration of 10% methanol as an ideal composition for the conservation solution of microorganisms. Similarly, several studies used concentrations of 9-10% methanol for fish embryos of species such as Rhinelepis aspera (Fornari et al, 2008), Colossoma macropomum (Pessoa et al, 2013), Brycon obignyanus (Fornari et al, 2014;Paes et al, 2014), Piaractus mesopotamicus (Lopes et al, 2014), and Piaractus brachypomus (Pessoa et al, 2015). In this study, we obtained an 80.85% hatching rate with 10% methanol for 6 h of cooling, and Pessoa et al (2013) observed an 88% hatching rate of Colossoma macropomum embryos treated with a 10% methanol solution.…”
Section: Methanol Concentration Dmso Concentration B Amentioning
confidence: 99%
“…Cooling and embryo freezing techniques, as well as cryoprotectant toxicity tests, have been studied in several species of native fish, in both species of economic interest and those endangered; some of the studied species are Piaractus mesopotamicus (Lopes et al, 2014), Piaractus brachypomus (Pessoa et al, 2015), Brycon orbignyanus (Fornari et al, 2014;Paes et al, 2014), and Prochilodus lineatus (Paula et al, 2014;Costa et al, 2017). Studies with ornamental fish species, such as Danio rerio, have also been conducted (Henn and Braunbeck, 2011;Kais et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for pelagic‐spawning species such as B . orbignyanus , knowledge on the reproductive cycle of captive broodstock is fundamental for the application of appropriate breeding protocols that can guarantee the supply of individuals for restocking actions (Agostinho et al, 2007; Castro et al, 2019; Fornari et al, 2014; Machado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%